Virtual Leadership and Team: Impacts on Generation Z Work Performance - Fanggidae, Rolland E.; Nursiani, Ni Putu; Salean, Debriana Y.; Radja, Susan M. M.; Pong, Nekidin (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
The COVID-19 pandemic has transformed work practices globally, including in Indonesia. Adapting to these changes has become crucial for organizational survival. This study aims to analyze the impact of virtual leadership on individual performance, assess the effectiveness of virtual teams in achieving organizational goals, and identify key factors mediating the relationship between virtual leadership, virtual teams, and performance. The research approach used is descriptive quantitative with a population of employees in organizations implementing virtual teams and leadership. Data were collected through questionnaires using simple linear regression with SPSS. The analysis results indicate that virtual leadership significantly influences the performance of virtual teams, explaining approximately 73.5% of the variation in performance. ANOVA shows that this regression model is statistically significant. Virtual leadership has a greater impact than team dynamics on performance. Factors such as geographical differences and the use of communication technology also affect team success. Leaders need to possess adaptive skills to face challenges in an electronically distributed work environment.